Fast track land reform in Matepatepa commercial farming area, Bindura district: effects on farm workers, 2000 – 2010 - Kufandirori, Joyline Takudzwa (University of the Free State, 2015)
This dissertation examines the effects of Zimbabwe’s Fast Track Land Reform Programme (FTLRP) on farm workers from 2000 to 2010. It looks at how farm workers fared during and after the process and how they dealt with the new conditions that ensued. It examines the nature of their relationships with their new employers and how the conditions under which they were employed changed and the impact of such changes on their livelihoods. The thesis also surveys the conditions of farm workers who took up other sources of livelihood after the land reform programme. It uses a case study of Matepatepa Commercial Farming area as a window to investigate the impact of the land reform exercise on farm workers in Zimbabwe. Matepatepa is located about 22 kms north of Bindura, Mashonaland Central’s provincial capital. The thesis mainly utilises narratives from farm workers in Matepatepa to explain the nature of their participation in the land reform programme and examines their relationship with some of the players who were central to the process, for example, war veterans, the government and other peasant farmers. In order to obtain a clearer understanding of the effects of the reform on farm workers’ livelihoods, the study also focuses on their conditions before the land reform and how they nurtured and developed their relations with their employers. It investigates the impact of the FTLRP in the context of the wider nature of Zimbabwe’s political and economic environment and assesses the impact of Zimbabwe’s political economy in shaping farm workers’ reactions to the changes brought about by the land reform exercise. The study acknowledges the fraught political background within which the land reform programme was carried out and consequently investigates the effect of such a background in determining the parameters within which farm workers could manoeuvre.

Hierdie verhandeling ondersoek die uitwerking van Zimbabwe se Versnelde Grondhervormingsprogram (Fast Track Land Reform Programme – FTLRP) op plaaswerkers tussen 2000 en 2010. Daar word gekyk hoe plaaswerkers gedurende en na afloop van die proses gevaar het, en hoe hulle die nuwe toestande wat daaruit voorgespruit het, hanteer het. Die aard van hul verhouding met hul nuwe werkgewers, veranderinge in hul indiensnemingstoestande, en die impak hiervan op hul lewensbestaan word ondersoek. Die verhandeling kyk ook na die toestande van plaaswerkers wat ná die grondhervormingsprogram ‘n ander bestaan opgeneem het. ‘n Gevallestudie van Matepatepa Kommersiële Landbouarea word as toegangspunt gebruik om die uitwerking van grondhervorming op plaaswerkers in Zimbabwe te ondersoek. Matepatepa is ongeveer 22 km wes van Bindura, Mashonaland Sentraal se provinsiële hoofstad, geleë. Die verhandeling maak hoofsaaklik van die vertellings van plaaswerkers in Matepatepa gebruik om die aard van hul deelname aan die grondhervormingsprogram te verduidelik, en ondersoek ook hul verhouding tot hoofrolspelers in dié proses, byvoorbeeld oorlogsveterane, die regering en ander kleinboere. Ten einde ‘n duideliker begrip van die hervormings se uitwerkings op plaaswerkers se bestaan te verkry, fokus hierdie studie ook op hul toestande vóór die grondhervormings en hoe hulle hul betrekkinge tot hul werkgewers gekoester en ontwikkel het. Die impak van die FTLRP binne die breër konteks van Zimbabwe se politieke en ekomiese omgewing word ondersoek, en die manier waarop Zimbabwe se politieke ekonomie plaaswerkers se reaksies op die veranderinge meegebring deur grondhervorming gevorm het, word beoordeel. Hierdie navorsing gee erkenning aan die gespanne agtergrond waarteen die grondhervormingsprogram uitgevoer is, en ondersoek daarom die rol wat hierdie agtergrond gespeel het om plaaswerkers se speelruimte te bepaal.
Dissertation (M.A. (Centre for Africa Studies))--University of the Free State, 2015
Keywords: Land reform; Violence; Labour; Livelihoods; Farm workers